Respuesta morfo-agronómica de 8 cultivares de fréjol arbustivo (Phaseolus vulgaris l.), en la granja Laguacoto III, cantón Guaranda, provincia Bolívar - Cadena Gómez, Carlos Lizandro (2021)
The cultivation of beans worldwide occupies a predominant place especially because it is constituted as an economical source of protein, carbohydrates, fiber, minerals and is also key in agroecological production models of small and medium farmers by Biological Fixation of Nitrogen (FBN). In Ecuador and particularly in the interim valleys of the high lands, the cultivation of shrub beans is a very important component of Local Production Systems (SPL), for the contribution to food security and sovereignty. This research was carried out at the Laguacoto III Experimental Farm of Bolivar State University, which is at an altitude of 2640 m. The objectives were: (i) Identify the main descriptors morphological of eight shrub bean accessions, (ii) Evaluate the main agronomic components, (iii) Select the best arbusive beans accessions and (iv) Generate a promissory germplasm database or for this agroecological zone. The treatments constituted eight cultivars of shrub beans from the Legume Program of INIAP Santa Catalina. Random Complete Block Design was applied with eight treatments and four repetitions. The main morphological descriptors and agronomic components were evaluated. Variance analysis was performed and the Tukey test was applied to compare the averages. The agronomic response of shrub beans germplasm was very different in this agroecological zone. There was variability of treatments in relation to morphological descriptors: main and secondary color of pods and grain, shape and brightness of the grain. The most important agronomic components that had highly significant differences between treatments were: incidence and severity of foliar diseases, growing cycle, pods per plant, length of pods, grains per pod, weight of one hundred dried grains, number of seeds per kilogram, grain diameter and dry grain yield at 13% humidity. The best accesses for its relevant agronomic behavior in this agroecological zone were treatments: T5 (Red Spotted Line - 1), T6 (Red Spotted Line - 6), T7 (Spotted Red Line - 7) and T8 (INIAP 484 Variety Red Spotted). Finally, this study validated and selected promising arbusive beans germplasm for the diversification of SPL and contributed to improving economic income and food security.